Synthetic Approaches to Zetekitoxin AB, a Potent Voltage-Gated Sodium Channel Inhibitor - Adachi, Kanna (Mar Drugs, 2019)
Voltage-gated sodium channels (Na(V)s) are membrane proteins that are involved in the generation and propagation of action potentials in neurons. Recently, the structure of a complex made of a tetrodotoxin-sensitive (TTX-s) Na(V) subtype with saxitoxin (STX), a shellfish toxin, was determined. STX potently inhibits TTX-s Na(V), and is used as a biological tool to investigate the function of Na(V)s. More than 50 analogs of STX have been isolated from nature. Among them, zetekitoxin AB (ZTX) has a distinctive chemical structure, and is the most potent inhibitor of Na(V)s, including tetrodotoxin-resistant (TTX-r) Na(V). Despite intensive synthetic studies, total synthesis of ZTX has not yet been achieved. Here, we review recent efforts directed toward the total synthesis of ZTX, including syntheses of 11-saxitoxinethanoic acid (SEA), which is considered a useful synthetic model for ZTX, since it contains a key carbon–carbon bond at the C11 position.